Simulator-Based Modeling for Complex Systems : Case of Blast Furnace - TSUMURA, Kouji; SASAKI, Tsuyoshi (Transactions of the Japan Society of Mechanical Engineers Series C, 1999)
In this paper, we propose a method to give models of complex systems for controller design by using numerical simulators. We apply this method to a two-dimensional region simulator for blast furnace and show a process of leading a model for control. Furthermore we compare the dynamics of the model with the simulator and analyze the performance of this method.